Microstructure and high-temperature oxidation behaviors of surface layer on TA2 pure titanium by boriding and aluminizing two-steps method. Issue 4 (15th February 2022) - Lu, Yaoping; Qu, Deyi; Duan, Yonghua; Peng, Mingjun
Abstract: The surface layer on pure TA2 titanium was manufactured using boriding and aluminizing two-step methods. High-temperature oxidation experiments were carried out at 600 °C, 700 °C, and 800 °C for 100 h. Microstructure characterization of the surface layer was investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM). After 1050°C-4 h boriding and 1050°C-4 h aluminizing, the composite layer from the surface to the matrix consists of a TiB2 layer, TiB whisker + Al3 Ti layer, Al3 Ti layer, and diffusion layer. The Al3 Ti layer could effectively protect the matrix, and thus, the borided and aluminized pure titanium shows excellent high-temperature oxidation resistance.